Atractylenolide I Inhibits NLRP3 Inflammasome Activation in Colitis-Associated Colorectal Cancer via Suppressing Drp1-Mediated Mitochondrial Fission - Qin, Yao; Yu, Yanwei; Yang, Chendong; Wang, Zhuien; Yang, Yi; Wang, Chongxu; Zheng, Qiusheng; Li, Defang; Xu, Wenjuan (Frontiers in Pharmacology, 2021)
Inflammatory bowel disease (IBD) is an important high-risk factor that promotes the occurrence and development of colon cancer. Research on the mechanism of regulating NLRP3 can provide potential targets for treating NLRP3 inflammasome–related diseases and changing the inflammatory potential of immune cells. In this study, the effects of atractylenolide I on colitis-associated CRC (caCRC) and inflammasome activation were investigated both in vivo and in vitro. Furthermore, the role of atractylenolide I on Drp1-mediated mitochondrial fission was analyzed via Western blotting and transmission electron microscopy (TEM). Moreover, the Drp1 overexpression lentiviral vector was used to study the role of Drp1 on the signaling mechanisms of atractylenolide I. Atractylenolide I treatment significantly reduced the cell viability of human HCT116 and SW480 cells and induced apoptosis, and effectively inhibited colon tumors in the AOM/DSS mouse model. The reduction of NLRP3 inflammasome activation and excessive fission of mitochondria mediated by Drp1 were associated with the administration of atractylenolide I. Upregulation of Drp1 reversed the inhibitory effect of atractylenolide I on the activation of NLRP3 inflammasomes. Overexpressing the Drp1 expression counteracted the restraint of atractylenolide I on the release of IL-1β of LPS/DSS-stimulated BMDMs. Atractylenolide I inhibited NLRP3 and caspase-1 expression in mice BMDMs, with no influence in the Drp1-overexpressed BMDMs. These results demonstrated that atractylenolide I inhibits NLRP3 inflammasome activation in colitis-associated colorectal cancer via suppressing Drp1-mediated mitochondrial fission.